PENGELOLAAN PEMBELAJARAN PAI DI MI AL-FALAH MUNCAK - Hudaefah; Heriyanto; Hikmatul Maulida; Siti Kholifah; Yusni Kustiyah; Ami Latifah (UNISAN JURNAL, 2023)
This exploration plans to depict the administration of PAI learning at MI Al Falah Muncak. This kind of exploration utilizes a subjective expressive strategy. The examination subjects were school chiefs, educational plan delegates, PAI educators and understudies. The information assortment procedures utilized were interview strategies, perception and documentation studies. Information investigation utilizes intelligent examination. The examination results show that the educational program is arranged in light of the public educational plan joined with the strict educational program. The substance of the strict educational program should be visible from this school booking PAI (Islamic Strict Instruction) learning for 12 hours, in particular 2 hours every one of religion, 2 hours of fiqh and fundamental abilities, and 8 hours of the Al-Qur'an. O'clock. eye to eye 30 minutes. MI Al Falah Muncak learning the executives is brought out through arranging, putting together, carrying out and assessing.